2018
DOI: 10.3389/fpls.2018.00621
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Proteomic Analyses of Molybdenum- and Ethylene-Responsive Mechanisms in Rubber Latex

Abstract: Molybdenum (Mo) is an essential micronutrient in many plants. In the rubber tree Hevea brasiliensis, Mo application can reduce the shrinkage of the tapping line, decrease tapping panel dryness, and finally increase rubber latex yield. After combined Mo with ethylene (Eth), these effects become more obvious. However, the molecular mechanism remains unclear. Here, we compared the changed patterns of physiological parameters and protein accumulation in rubber latex after treated with Mo and/or Eth. Our results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Fructokinase is a kinase that catalyzes the transfer of phosphate groups to fructose and can phosphorylate the sugar at the C-1 position, and thus is considered as one of the rate-limiting enzymes of glycolysis [ 54 ]. Recent rubber latex proteomics data revealed that fructokinase can be induced by ethylene treatment [ 55 ], but in this study, we found this enzyme can be glycosylated and its abundance was decreased after ethylene stimulation for five days ( Table S2 ). Aldehyde dehydrogenase is a kind of oxidizing enzyme that is involved in detoxification of both exogenous and endogenous aldehyde substrates through NAD(P) + -dependent oxidation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Fructokinase is a kinase that catalyzes the transfer of phosphate groups to fructose and can phosphorylate the sugar at the C-1 position, and thus is considered as one of the rate-limiting enzymes of glycolysis [ 54 ]. Recent rubber latex proteomics data revealed that fructokinase can be induced by ethylene treatment [ 55 ], but in this study, we found this enzyme can be glycosylated and its abundance was decreased after ethylene stimulation for five days ( Table S2 ). Aldehyde dehydrogenase is a kind of oxidizing enzyme that is involved in detoxification of both exogenous and endogenous aldehyde substrates through NAD(P) + -dependent oxidation.…”
Section: Discussionmentioning
confidence: 60%
“…Its gene expression was up-regulated in the latex of a tapping panel dryness [ 57 ] and a high-yielding rubber tree [ 54 ]. Proteomics analyses revealed that this protein is highly abundant in the washed solutions of rubber particles [ 48 ] and was significantly induced in rubber latex after ethylene application [ 55 ]. Another enzyme, glutamine synthetase, plays an important role in metabolizing nitrogen by catalyzing the reaction of condensation of glutamate and ammonia to form glutamine, and the glutamine–glutamate synthase cycle might be the major pathway for the amino acid and protein synthesis required for natural latex regeneration [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems allow trees to be tapped in a lesser frequency or lesser amount of bark consumption and ensure sustained production in rubber plantations (Njukeng et al, 2011). Ethephon is used as the yield stimulant along with the LIH systems in order to recover the yield loss due to the reduction of harvesting intensity (Gao et al, 2018). Ethephon is a kind of plant growth regulator that penetrates into the plant tissues and decomposes to produce ethylene that increases activities of anabolic physiological processes such as biosynthesis of rubber and related proteins (Tseng et al, 2000;Coupe and Chrestin, 1989).…”
mentioning
confidence: 99%
“…Furthermore, effect of ethephon on cell membrane permeability results in decrease of laticiferous vessel obstruction (Zhu and Zhang, 2009). As a result of delaying the plugging of latex vessels, the duration of latex flow is increased (Emuedo et al, 2017;Gao et al, 2018). Thereby the yield per tapping is increased (Kudaligama et al, 2013).…”
mentioning
confidence: 99%